FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DAN FIRM VALUE YANG TERDAFTAR DI BEI - Adeline Connie, Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to analyze the effect of firm size and profitability on debt policy and firm value. This study used a sample of 66 from 162 manufacturing companies selected using purposive sampling method for a total of 198 data in three years listed in the Indonesia Stock Exchange for the year 2015-2017. Data processing techniques used are Eviews version 9.0. The statistical method used to test the research hypothesis is the multiple linear regression method in which the test is performed on panel data. The result of this research shows that firm size has no significant effect on debt policy, meanwhile profitability has a positive significant effect on debt policy. The results shows that firm size and profitablity have positive significant effect on firm value too while debt policy has a negative significant effect on firm value.